Leveraging social protection to support women’s and girls’ climate resilience in low- and middle-income countries - Hidrobo, Melissa; Bryan, Elizabeth; Läderach, Peter R.D.; Mueller, Valerie; Navia, Bianca; Nesbitt-Ahmed, Zahrah; Roy, Shalini (International Food Policy Research Institute, 2023)
Climate change is hitting hardest some of those already most vulnerable, Rapidly exacerbating inequalities, including gender inequality, Climate action is urgently needed – at scale, and with a gender lens, Growing interest in the potential of social protection, Social protection programs reach billions of resource-poor people globally, Existing vast literature suggests substantial potential to support climate resilience – but little evidence framed explicitly around climate (and even less around gendered climate impacts), The Sharm El Sheikh Implementation Plan for COP27 (UNFCCC, 2022): explicitly mentions social protection as an implementation pathway for responding to the climate crisis, highlights the importance of ensuring gender-responsive implementation of climate action,. but it does not bring together these themes in its recommendations